PENYALAHGUNAAN OBAT BATUK ADITUSIN DI KALANGAN REMAJA - Remi Aldi; Abdul Munir (UIR PRESS, 2020)
Abuse of Aditusine cough medicine by adolescents in Belilas Village, Kec. Seberida, Kab. Inhu (Riau), as a social phenomenon that grows in the midst of people's lives. By using the Differential Association theory approach and Techniques of Neutralization as an analytical knife and a qualitative approach as the method, this research finds a conclusion; there has been a shift in the use of drugs from previously illegal drugs (shabu, marijuana, etc.) to legal drugs (Aditusine cough medicine), as a way to avoid prosecution from both a legal and social perspective.